2018
DOI: 10.1186/s13071-018-3141-9
|View full text |Cite
|
Sign up to set email alerts
|

Can the pyruvate: ferredoxin oxidoreductase (PFOR) gene be used as an additional marker to discriminate among Blastocystis strains or subtypes?

Abstract: BackgroundBlastocystis spp. are the most prevalent intestinal eukaryotes identified in humans, with at least 17 genetic subtypes (ST) based on genes coding for the small-subunit ribosomal RNA (18S). It has been argued that the 18S gene should not be the marker of choice to discriminate between STs of these strains because this marker exhibits high intra-genomic polymorphism. By contrast, pyruvate:ferredoxin oxidoreductase (PFOR) is a relevant enzyme involved in the core energy metabolism of many anaerobic micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 55 publications
(52 reference statements)
1
15
0
Order By: Relevance
“…not show high genetic diversity compared to the ssu rRNA locus (Figure 2, Supplementary material Table S1) and showed a grouping in the phylogenetic reconstruction that was relatively associated with the STs and the collection areas (Figures 3 and 5). This suggested that this gene was probably under different evolutionary forces, which were similar to the PFOR gene reported in the Mexican samples [26]. Also, it was important to consider that ribosomal genes were highly utilized in eukaryotes and required a large production of ribosomes in times of massive growth, that could encode hundreds of copies of their transcriptional units [55], leading to recombination events and potentially greater diversity compared to the constitutive metabolic genes, which did not require high variation in order to maintain their function.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…not show high genetic diversity compared to the ssu rRNA locus (Figure 2, Supplementary material Table S1) and showed a grouping in the phylogenetic reconstruction that was relatively associated with the STs and the collection areas (Figures 3 and 5). This suggested that this gene was probably under different evolutionary forces, which were similar to the PFOR gene reported in the Mexican samples [26]. Also, it was important to consider that ribosomal genes were highly utilized in eukaryotes and required a large production of ribosomes in times of massive growth, that could encode hundreds of copies of their transcriptional units [55], leading to recombination events and potentially greater diversity compared to the constitutive metabolic genes, which did not require high variation in order to maintain their function.…”
Section: Discussionsupporting
confidence: 74%
“…But, due to the unknown role of this microorganism inside the gut, it has been proposed to explore additional markers with different evolutionary rate in order to elucidate what is happening in these populations. A few authors, have reported the need for use of other genes or non-coding regions of the genome, such as the internal transcribed spacers (ITS) [27], the use of single copy markers from MROs, which allowed for the detection of coinfections even in the same ST [25] or the use of the PFOR gene that generated clades that were different from the STs, because they were subject to different selective pressures that showed an evolutionary history different from that of the ssu rRNA gene [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review of Blastocystis in the different countries of North and South America identified 39 articles that met the selection criteria, for which the distribution of Blastocystis and its subtypes was analyzable. However, only nine countries in North and South America (Argentina [9, 13], Brazil [9, 11, 21–31], Bolivia [9, 32, 33], Colombia [2, 9, 10, 34–37], Chile [38], Ecuador [9, 39], USA [17, 36, 4047], Peru [9] and Mexico [4850] were found to have carried out this type of study. From these countries, Blastocystis was identified in samples from both human and other hosts.…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies conducted in North and South America, the most widespread subtypes we collated were ST1 and ST2, which were present in the samples from eight of the nine countries that were studied [2, 911, 17, 2127, 2939, 42, 43, 4550]. Subsequently, ST3 was found in seven of the nine countries [2, 911, 13, 17, 21, 23–25, 27, 30, 31, 33–37, 39, 42, 43, 4650].…”
Section: Resultsmentioning
confidence: 99%